2018
DOI: 10.18488/journal.62.2018.56.201.218
|View full text |Cite
|
Sign up to set email alerts
|

Firm-Level Investment Decisions Under Uncertainty and Irreversibility in Zimbabwes Private Firms

Abstract: Zimbabwe"s business operating environment is abounding with both micro and macro uncertainties that regularly impact on firm-level investment decisions. Under uncertainty and irreversibility private firms are forced to integrate into their investment appraisals and decisions some expectations regarding future product demand and prices, likely returns on fixed capital investment, expected margins, cost of capital expectations and cash flow projections. These important issues are not known with definitive assura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…The solution that community seeks for this problem is to collect used oil and come up with the easily chemical processes to produce its as "Esther" with similar properties to diesel. So, the community can use its instead of diesel oil called biodiesel which it can help community to reduce the amount of waste, reduce the pollution and also produce the other biodiesel used for agricultural machine (Muzurura, 2018;Ali and Haseeb, 2019). Community biodiesel should be a collaboration of government and community with the goal of transferring knowledge about biodiesel production technology because the raw materials used in the production of biodiesel can be obtained from the local sources such as oil, jatropha oil, used vegetable oil and from various oil crops to be used as fuel for agricultural machinery immediately.…”
Section: Research Resultsmentioning
confidence: 99%
“…The solution that community seeks for this problem is to collect used oil and come up with the easily chemical processes to produce its as "Esther" with similar properties to diesel. So, the community can use its instead of diesel oil called biodiesel which it can help community to reduce the amount of waste, reduce the pollution and also produce the other biodiesel used for agricultural machine (Muzurura, 2018;Ali and Haseeb, 2019). Community biodiesel should be a collaboration of government and community with the goal of transferring knowledge about biodiesel production technology because the raw materials used in the production of biodiesel can be obtained from the local sources such as oil, jatropha oil, used vegetable oil and from various oil crops to be used as fuel for agricultural machinery immediately.…”
Section: Research Resultsmentioning
confidence: 99%
“…For instance, Caballero (1991) and McDonald and Siegel (1986) showed that imperfect competition negatively intensifies the relationship between investment uncertainty. A monopolistic firm can simply delay its investment as an investment opportunity is always available at any time when it decides to do so (Muzurura, 2018). This argument may also apply to an oligopolistic firm, probably to a lesser extent.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Dissimilar investment models have been developed to assess corporate investment, since it is perceived that when investment projects are correctly valued, it will assist investors in making valuable decisions that could help a firm to make workable financial commitments for the survival of the firm via the channel of profitability or value creation. However, the prevailing net present value and discounted cash flow techniques seem inept in capturing all the important factors that could influence investment decisions (Muzurura, 2018), hence the consideration of the real options theory of investment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Credit risk is the kind of risks that bears losses due to the unexpected damage that is seen in the creditworthiness of counterparties. Otherwise, credit or the other party risk belongs to the opportunity that a borrower of the source of a financial instrument from the side of the country, a company, or an individual will not be able to repay the principal and the investment-related cash flow related to the conditions, terms, and obligations determined in a credit agreement (Bessis, 2009;Muzurura, 2018).…”
Section: Introductionmentioning
confidence: 99%